Quality Analysis of an Interactive Programming Learning Platform Based on ISO/IEC 25010 Using a String-Matching Approach on User Reviews - Mochamad Chandra Saputra; Satrio Agung Wicaksono; Satrio Hadi Wijoyo; Prasetya Naufal Rahmandita; Buce Trias Hanggara (J-Intech (Journal of Information and Technology))
This study aims to analyze user perceptions of Quality in Use of the Khan Academy e-learning platform, focusing on two key characteristics defined in the ISO/IEC 25010 standard: satisfaction and efficiency. Based on the analysis of user review data, there is a clear difference in volume between the two aspects: 539 reviews (65%) reflected the satisfaction aspect, while only 290 reviews (35%) were related to efficiency. This indicates that users are approximately 1.86 times more likely to comment on satisfaction than on efficiency. For satisfaction, most of reviews were positive (420 reviews, or 77.9%), while 119 reviews (22.1%) expressed negative sentiments. These results suggest that most users are satisfied with their experience using Khan Academy, particularly due to factors such as flexible access time, user convenience, and the wide availability of learning materials. In contrast, the efficiency- related reviews exhibited a more even distribution, with 154 positive reviews (53.1%) and 136 negative reviews (46.9%). This closer balance indicates that while some users appreciate the platform's performance, others report encountering technical issues, including slow access speeds, navigation difficulties, and system instability. Overall, user perception of the Khan Academy e-learning system is generally positive, especially regarding satisfaction. However, the findings also underscore the importance of addressing technical performance challenges to improve efficiency and ensure a seamless learning experience. These insights provide a valuable basis for the development of user-centered e-learning systems and contribute to the evaluation of system quality from the Quality in Use perspective.